Clinical practice on intra-operative fluid therapy in Poland: A point prevalence study. Issue 17 (April 2020) - Szczepańska, Anna J.; Pluta, Michał P.; Krzych, Łukasz J.
Abstract : Abstract: Intra-operative fluid therapy (IFT) is the cornerstone of peri-operative management as it may significantly influence the treatment outcome. Therefore, we sought to evaluate nationwide clinical practice regarding IFT in Poland. A cross-sectional, multicenter, point-prevalence study was performed on April 5, 2018, in 31 hospitals in Poland. Five hundred eighty-seven adult patients undergoing non-cardiac surgery were investigated. The volume and type of fluids transfused with respect to the patient and procedure risk were assessed. The study group consisted of 587 subjects, aged 58 (interquartile range [IQR] 40–67) years, including 142 (24%) American Society of Anesthesiology Physical Status (ASA-PS) class III+ patients. The median total fluid dose was 8.6 mL kg −1 h −1 (IQR 6–12.5), predominantly including balanced crystalloids (7.0 mL kg −1 h −1, IQR 4.9–10.6). The dose of 0.9% saline was low (1.6 mL kg −1 h −1, IQR 0.8–3.7). Synthetic colloids were used in 66 (11%) subjects. The IFT was dependent on the risk involved, while the transfused volumes were lower in ASA-PS III+ patients, as well as in high-risk procedures ( P  < .05). The practice of IFT is liberal but is adjusted to the preoperative risk. The consumption of synthetic colloids and 0.9% saline is low.